2002
DOI: 10.1097/00129492-200203000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Retrosigmoid Approach for Small and Medium-sized Acoustic Neuromas

Abstract: The retrosigmoid approach is a safe and reliable approach in random patients with small and medium-sized acoustic neuromas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 24 publications
2
58
1
1
Order By: Relevance
“…In some instances, hearing is even improved after AN resection when the auditory nerve could be preserved [20]. In our patient, the surgical approach was highly beneficial to decompress the brain stem and to preserve the facial and auditory nerves as similarly reported recently [21]. The residual hearing is usually limited by the size of the schwannomas; thus, the compromised blood supply and their high invasiveness in contrast to the 'common' ANs of the cerebellopontine angle or to NF-1 patients [22][23][24][25].…”
Section: Discussionsupporting
confidence: 74%
“…In some instances, hearing is even improved after AN resection when the auditory nerve could be preserved [20]. In our patient, the surgical approach was highly beneficial to decompress the brain stem and to preserve the facial and auditory nerves as similarly reported recently [21]. The residual hearing is usually limited by the size of the schwannomas; thus, the compromised blood supply and their high invasiveness in contrast to the 'common' ANs of the cerebellopontine angle or to NF-1 patients [22][23][24][25].…”
Section: Discussionsupporting
confidence: 74%
“…It was suggested that adjunctive use of endoscopes increases the hearing preservation rate both in retrosigmoid and middle fossa approaches [8,9] . The hearing preservation rate was 24.4% in our series.…”
Section: Discussionmentioning
confidence: 99%
“…For ECOG, electrodes are typically positioned transtympanically on the middle ear promontory of the pathological ear. 45,53,65,80,95,96,101,123 Reference and ground electrodes are placed on the ipsilateral earlobe and on the forehead, respectively. 64,113,114,149 A foam ear plug not only holds the electrode firmly in place but also impedes foreign substances from breaching into the ear canal.…”
Section: Electrocochleography and Direct Cnapsmentioning
confidence: 99%
“…[3][4][5][6]15,23,25,45,49,56,58,61,65,67,112,115,117,118,124,130,131 However, IONM may demonstrate improvements in structural and functional preservation of the cranial nerves during these operations. 139,148 Several IONM techniques have been developed and evaluated with particular focus on CN VII and VIII preservation.…”
mentioning
confidence: 99%